Dimensi Spiritual Kebudayaan di Tengah Relasi yang Timpang antara Utara dan Selatan - Tasrif, Muh. (el Harakah: Jurnal Budaya Islam, 2008)
Moslem society as a part of the population of the south world, culturally, is in the influence of the hegemony of non-moslem culture, mainly, European, American, and Australian as parts of the north world population. Until the mid twentieth century, the hegemony existed in the form of military imperialism. Meanwhile, in the post mid twentieth century the hegemony changed into cultural imperialism in many areas, such as social, economic, social and even art. The countries of the south world have really done some efforts to face the neo imperialism, but have not suceeded well. Therefore, more serious effort should be done to face the neo imperialism, that is the creativity to make the European and American cultural products as materials that can be creatively rearranged and matched with the local culture. In the creative process the spiritual dimension of culture should become the basis of cultural production process at present and in the future to create a fair relation. The use of spiritual dimension of culture can create new cultural products. In turn, the cultural products of the south world will exist, and finally they can be exchanged with the products of the north world. This is what China is doing with its developing economic power to balance out the domination of Europe and America. The same hopefully appears from the Islam world although it needs more serious cultural works. According to Faisal Ismail, the awakening of Islam and its culture depend on the moslem themselves and their cultural works. Masyarakat Muslim sebagai bagian dari populasi dunia selatan, secara kultural, berada dalam pengaruh hegemoni budaya non-muslim, terutama Eropa, Amerika, dan Australia sebagai bagian dari populasi dunia utara. Sampai pertengahan abad ke-20, hegemoni itu ada dalam bentuk imperialisme militer. Sementara itu, pada pertengahan abad ke-20 hegemoni berubah menjadi imperialisme budaya di banyak bidang, seperti sosial, ekonomi, sosial dan bahkan kesenian. Negara-negara di dunia selatan telah benar-benar melakukan beberapa upaya untuk menghadapi imperialisme neo, namun belum berhasil dengan baik. Karena itu, usaha yang lebih serius harus dilakukan untuk menghadapi neo imperialisme, yaitu kreativitas membuat produk budaya Eropa dan Amerika sebagai bahan yang bisa ditata ulang secara kreatif dan disesuaikan dengan budaya lokal. Dalam proses kreatif dimensi spiritual budaya harus menjadi dasar proses produksi budaya saat ini dan di masa depan untuk menciptakan hubungan yang adil. Penggunaan dimensi spiritual budaya bisa menciptakan produk budaya baru. Pada gilirannya, produk budaya dunia selatan akan ada, dan akhirnya mereka bisa dipertukarkan dengan produk-produk dari dunia utara. Inilah yang dilakukan China dengan kekuatan ekonomi yang berkembang untuk mengimbangi dominasi Eropa dan Amerika. Hal yang sama semoga muncul dari dunia Islam meski membutuhkan karya budaya yang lebih serius. Menurut Faisal Ismail, kebangkitan Islam dan budayanya bergantung pada umat Islam sendiri dan karya budaya mereka.